Nalchik District during the Russian Revolution (1917-1920): The Chaotization of Violence - Osman A. Zhansitov (Кавказология)
This article explores the impact of the revolutionary situation in the Nalchik District on the dynamics and nature of spontaneous violence and identifies factors that provoked its growth. It notes that in conditions of systemic political crisis, regimes in power lose their monopoly on violence, which is then employed by representatives of various societal layers to settle scores with “class enemies.” Moreover, militarized structures subordinate to the authorities, such as regular army units or popular militias, often used unauthorized repressive practices. This paper emphasizes that acts of spontaneous violence were also provoked by the authorities themselves, who, through propaganda, encouraged the masses to fight against political opponents and social groups loyal to them. The article also discusses attempts by the authorities to contain the growth of spontaneous violence. The Soviet administration in the Nalchik District sought to curb the excessive zeal of commanders of various revolutionary units and to limit their actions within the framework of “socialist legality.” The White administration, aiming to extinguish the social confrontation that arose from the arbitrary attempts by residents harmed by the Bolsheviks to seek compensation, created mechanisms to satisfy their initiatives within the legal framework.